Systematic review: mechanism of relative age effect in sport - Jasni, Nur Raifana Shazana; Tengku Kamalden, Tengku Fadilah; Jakiwa, Jorrye; Wazir, Mohd Rozilee Wazir Norjali (SPED, 2022)
The importance of talent identification (TID) in sports development could not be denied where it could be a change on career pathway for an athlete, and this is also might cause the talent loss when scouting the team and this are very crucial at grassroots to elite youth level. The relative age effect (RAE) has been studied widely in sports where there is an advantages and disadvantages occurred and lead to the talent loss. Many of the sports does not have a standardized TID process which most of them are based on try and error and expose to biases. Literature on this paper was obtained from computer based sources. This research paper will discuss and elaborate more on the mechanism that might be affecting the present of RAE which are maturity, playing position, gender and performance and its possible solution which is important for the future development to help researchers, sports & health professional, coaches and athletes understand the concept of RAE and the solution selected.